Security & safety issues and endogenous security for intelligent connected vehicles - JIA Hongying; LI Yufeng (Dianxin kexue)
With the rapid development of vehicle-road-cloud integrated system (VRCIS), physical space and cyber space were deeply intertwined, resulting in a brand-new transformation of automobile safety. New challenges arise in the integrated security domain, where safety, security and information security were deeply overlapped. Based on a comprehensive analysis the integrated security problem of intelligent connected vehicle (ICV) and limitations of existing security defense methods, guided by the endogenous security existence theorem, a dynamics heterogeneous redundancy (DHR) based endogenous security construction technology was proposed to solve the triple security overlap problem with integrated construction effects, achieving known and unknown threat defense without relying on prior knowledge. The results of a large number of endogenous safety white-box pile injection tests show that the endogenous safety DHR architecture had 100% differential mode suppression capability. In order to promote the overall goal of achieving endogenous safe boarding, a close range planning scheme for intelligent connected vehicles with the core of “pre blocking, mid defense, and post traceability” had also been explored.